Coronary artery bypass grafting in idiopathic myelofibrosis: a case report. - (:unkn) unknown (My University, 2007)
The concomitant presence of myeloproliferative disorders and the need for coronary artery bypass surgery is a surgical dilemma. Thrombosis and hemorrhage can cause difficult problems and might require different approaches during and after surgery. We report a patient who had idiopathic myelofibrosis and underwent a successful coronary artery bypass surgery.